Perceptions of occupational health risks, illnesses and coping strategies among workers in a factory in Savar, Bangladesh - Iacobelli, M.; Chowdhury, Morseda; Nagbe, Thomas Knue (BRAC University, 2016)
Includes bibliographical references (page 29).